Hemorragia peri-intraventricular em recém-nascidos pré-termo de muito baixo peso ao nascer: perfil metabolômico e fatores de risco - Tavolone, Mariana Gonçalves Gomes (2021)
Introduction: Intraventricular hemorrhage (IVH) is a frequent morbidity in the neonatal period, especially in preterm infants and may cause, in a long term, motor impairment and/or neurodevelopmental delay in several degrees depending on the severity of brain damage. The multifactorial pathophysiology of IVH is a matter of discussion in the literature and metabolomics analysis has been proposed as a way to collaborate in its elucidation. Objective: to evaluate the blood metabolomic profile of preterm infants with very low birth weight and identify the metabolites associated with the presence of intraventricular hemorrhage at two days of life; identify the risk factors associated with the occurrence of intraventricular hemorrhage between 2 and 7 days of life. Method: This is a cross-sectional study, in which newborns with very low birth weight and with a gestational age below 34 weeks, born between June 2017 and August 2019, were included. It was not included neonates with congenital malformations, genetic syndromes, chromosomopathies, twins, those who progressed to death in the first 48 hours of life, who did not undergo ultrasound examination on the 2nd day of life and those who did not have blood samples collected on the 2nd day of life. The diagnosis of intraventricular hemorrhage was performed using transfontanellar ultrasound between 48 and 72 hours of life and repeated at 7 days of life. The classification of Papille was adopted in the diagnosis and classification of IVH. Clinical and demographic data were obtained from maternal and infants medical records. For the global metabolomic analysis, blood samples were collected on the second day of life of the newborn. Statistical analyzes were performed with log2 transformed values. The t test, Mann Whitney test, chi-square test or Fisher's exact test were applied. Multivariate analysis was performed using binary logistic regression. It was considered as statistical significance p<0.05. Results: During the study, 253 eligible infants were born. In the analysis of the metabolomic profile, 129 preterm infants were included, and 33 (25.5%) presented IVH at two days of life. The neonates with IVH were more frequently resuscitated in the delivery room (81.8% vs 62.5%; p=0.041), presented lower gestational age at birth (27.1 vs 28.5 weeks; p=0.003) and higher SNAP-PE II score (37 vs 25; p=0.017). In addition, received mechanical ventilation with more often (69.7% vs 36.5%; p=0.003) and with longer invasive mechanical ventilation time (48h vs 20h p<0.001), higher rates of exogenous surfactant use (94% vs 66.6%; p=0.002), early sepsis (15.2% vs 2.1%; p=0.04) and death (33% vs 15.6%; p=0.029). Concerning the metabolomic analysis, a higher expression of monoacylglycerol (OR = 0.942, 95% CI = 0.897; 0.990) and of 10Z, 13Z-nonadecadienoic acid (OR = 0.868, 95% CI = 0.795; 0.947) in preterm infants without IVH was observed. The concentration of β-isorenieratene was higher in those preterm infants with IVH (OR = 1.065, 95% CI = 1.003; 1.130). In addition, these preterm neonates received vasoactive drugs at a higher frequency (OR = 6.585, 95% CI = 2.008; 21.591). For the evaluation of factors associated with IVH between 2 and 7 days of life, 99 neonates with normal ultrasound at two days of life were included, and 17 (17.17%) of these had IVH at 7 days, 5 (29.4%) grade I, 9 (52.9%) grade II and 3 (17.6%) grade III. Gestational age (p=0.002) and birth weight (p=0.009) were lower among neonates with IVH. Neonates with IVH had a higher incidence of pneumothorax (p<0.001), patent ductus arteriosus (p=0.003), sepsis (p<0.001), need for vasoactive amines (p=0.018), blood transfusion (p=0.002), invasive mechanical ventilation (p=0.002) and death (p=0.03). In the binary logistic regression model, sepsis was associated with a higher occurrence of IVH (OR=4.081, 95% CI= 1.034 - 16.116, p-value = 0.045). Conclusion: The metabolomics analysis of the blood of preterm infants showed a difference in the blood concentration of three substances in neonates with IHV when compared to those without IHV, suggesting the needs for further studies to assist in the identification of important metabolomic pathways for the understanding of the pathophysiology of IHV and for the development of new strategies for prevention and treatment of this pathology. Moreover, this study confirmed the multifactorial etiology of IHV and identified sepsis as the main related risk factor, reinforcing that the knowledge of these factors is particularly important in the definition of strategies for the care of neonates in order to reduce the incidence of IHV.